Reversible redox cycling of well-defined, ultra-small Cu/Cu2O nanoparticles - Williams, C; Pike, S; White, E; Regoutz, A; Sammy, N; Payne, D; Shaffer, M (American Chemical Society, 2017)
Exceptionally small and well-defined copper (Cu) and cuprite (Cu2O) nanoparticles (NPs) are synthesized by the reaction of mesitylcopper(I) with either H2 or air, respectively. In the presence of sub-stoichiometric quantities of ligands, namely stearic or di(octyl)phosphinic acid (0.1-0.2 equivalents (equiv.) vs. Cu), ultra-small nanoparticles are prepared with diameters as low as ~2 nm, soluble in a range of solvents. The solutions of Cu NPs undergo quantitative oxidation, on exposure to air, to form Cu2O NPs. The Cu2O NPs can be reduced back to Cu(0) NPs using accessible temperatures and low pressures of hydrogen (135°C, 3 bar H2). This striking reversible redox cycling of the discrete, solubilized Cu/Cu(I) colloids was successfully repeated over 10 cycles, representing 19 separate reactions. The ligands influence the evolution of both composition and size of the nanoparticles, during synthesis and redox cycling, as explored in detail using vacuum-transfer aberration-corrected TEM, XPS and visible spectroscopy.